Notes on Abutilon (Malvaceae) in the Mediterranean and Macaronesia - Verloove, Filip (Hacquetia, 2025)
Recent field- and herbarium studies in the genus Abutilon in the Mediterranean and Macaronesia yielded some noteworthy results. The invasive South American weed A. grandifolium is reported for the first time from Algeria. A recent claim of A. grandiflorum from the Canary Islands is erroneous and referable to A. grandifolium. Historical records of the South African A. sonneratianum from Madeira are also discussed. This species is included in the list of invasive species in Portugal. However, it is shown that the invasive species in Portugal (Madeira) is A. grandifolium, not A. sonneratianum.
Keywords: alien plants; botanical classification; klasifikacija rastlin; Madeira; malvales; slezenovci; tujerodne rastline